(untitled) (World Journal of Current Medical and Pharmaceutical Research, 2022)
The present study was done with the aim to screen the anthelmintic activity of decoction containing Andrographis paniculata (Kalmegh), Azadirachta indica (Neem), Carica papaya latex using Pontoscolex corethrurus. The different concentrations (40%, 60% and 80%) of decoction were evaluated for determining the time of paralysis and the time of death of earthworms. Albendazole (10mg/ml) used as standard reference and normal saline as control. The data of the study revealed that the decoction at 80% concentration showed better anthelmintic activity compared to standard drug Albendazole.